Population Pharmacokinetics of Ropeginterferon Alfa-2b: A Comparison Between Healthy Caucasian and Chinese Subjects - Zhu, Min; Wang, Mei-xia; Li, Zi-ran; Wang, Wei; Su, Xia; Jiao, Zheng (Frontiers in Pharmacology, 2021)
Objective: To develop a population pharmacokinetic (PK) model for ropeginterferon alfa-2b and to compare its PK properties between Caucasian and Chinese populations. Methods: A population PK model was developed based on data from two phase I clinical trials conducted in Caucasian and Chinese individuals, to evaluate the influence of ethnicity on the PKs of ropeginterferon alfa-2b. Results: We included 456 observations from 30 healthy Caucasian subjects and 438 observations from 27 healthy Chinese subjects in the population PK analysis. The PKs of ropeginterferon alfa-2b were best described by a one-compartment quasi-equilibrium approximated target-mediated drug disposition model with first-order absorption and absorption lag times. The apparent clearance (CL/F) and volume of distribution of ropeginterferon alfa-2b in 70-kg subjects were 0.778 L/day and 2.32 L, respectively. Body weight was the only significant factor affecting the CL/F. There were no obvious ethnic differences in the PK properties of ropeginterferon alfa-2b, and predicted steady-state exposure was similar in the Chinese and Caucasian populations. Conclusion: No significant ethnic differences in ropeginterferon alfa-2b PKs were observed between the Chinese and Caucasian populations, indicating that Chinese individuals can be administered the same doses as Caucasians, from a PK perspective.